Frugal energy innovations for developing countries – a framework. Issue 1 (30th September 2016) - Numminen, Sini; Lund, Peter D.
Abstract: Frugal innovations have recently emerged to feature low‐cost technologies and business innovations to serve consumers in emerging markets and improve their quality of life. Although the concept of frugality is well known, the present literature on frugal energy innovations, or energy frugality, is scarce, which could lead to overlooking its true characteristics. Therefore, we propose a framework for defining energy frugality based on a detailed analysis of several low‐cost sustainable energy technologies. The five‐criteria assessment method developed will help to identify potential frugal energy innovations and will increase the adoption of these technologies through better matching to local needs. Fuel‐efficient biomass cooking stoves, small‐scale photovoltaic systems, and pico‐grids are examples of such frugal energy technologies. Abstract : Impact Statement The research conducted addresses the global energy challenge through the frugality concept, which represents a novel and affordable way to provide services to people living in developing countries. Energy frugality is based on effective use of local renewable energy and other resources. Here, we present a framework for identifying and developing frugal energy innovations. Wide dissemination of this concept may alleviate global energy poverty in a sustainable manner.